2005
DOI: 10.1091/mbc.e05-01-0081
|View full text |Cite
|
Sign up to set email alerts
|

PAK5 Kinase Is an Inhibitor of MARK/Par-1, Which Leads to Stable Microtubules and Dynamic Actin

Abstract: MARK/Par-1 is a kinase involved in development of embryonic polarity. In neurons, MARK phosphorylates tau protein and causes its detachment from microtubules, the tracks of axonal transport. Because the target sites of MARK on tau occur at an early stage of Alzheimer neurodegeneration, we searched for interaction partners of MARK. Here we report that MARK2 is negatively regulated by PAK5, a neuronal member of the p21-activated kinase family. PAK5 suppresses the activity of MARK2 toward its target, tau protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 53 publications
(89 reference statements)
4
70
0
3
Order By: Relevance
“…13 In CHO cells, PAK5 interacted with MARK2 and inhibited its effect on the microtubule and actin networks, promoting filopodia formation. 36 In accordance with previous studies, we found that PAK5 was expressed and localized at the focal adhesion on the side of the leading edge of CRC cells, which implied that PAK5 was involved in regulating CRC cell motility. Further study showed that overexpression of PAK5 in CRC cells reduced cell adhesion but enhanced cell migration on collagen type I.…”
Section: Discussionsupporting
confidence: 92%
“…13 In CHO cells, PAK5 interacted with MARK2 and inhibited its effect on the microtubule and actin networks, promoting filopodia formation. 36 In accordance with previous studies, we found that PAK5 was expressed and localized at the focal adhesion on the side of the leading edge of CRC cells, which implied that PAK5 was involved in regulating CRC cell motility. Further study showed that overexpression of PAK5 in CRC cells reduced cell adhesion but enhanced cell migration on collagen type I.…”
Section: Discussionsupporting
confidence: 92%
“…Its activity on several exogenous GFP fusion targets was negligible. Inactive PAK5-YFP (Matenia et al, 2005) and EB3-GFP (Stepanova et al, 2003) plasmids were described previously.…”
Section: Methodsmentioning
confidence: 99%
“…91 Inhibitory regulation of MARK can additionally be achieved by binding to PAK5 or to scaffolding proteins or by subcellular localization. 91,93 The activating MARKK is a member of the Ste20 family of kinases and phosphorylates MARK at a threonine residue in the activation loop. Other functions of MARKK/TAO-1 involve mitosis progression and MAPK/p38 signaling upon stress induced activation.…”
Section: Antiphosphorylation Strategiesmentioning
confidence: 99%